Socio-Economic Determinants and Preschool Environment as Predictors of Intelligence in Early Childhood: A Twin-based Study - Annu,; , Bimla Dhanda (Archives of Current Research International, 2025)
This study aimed to examine the relative influence of socio-economic factors and preschool environment on the intelligence of young children using a twin research design. Twin study design allows researchers to estimate the proportion of variance in intelligence due to genetics, shared environment, and non-shared environment. This study conducted in the Bhiwani and Hisar districts of Haryana, the study involved 150 pairs of monozygotic (MZ) and dizygotic (DZ) twins aged 3 to 6 years. Participants were selected through snowball sampling. Data were collected using a self-structured socio-economic questionnaire and the Early Childhood Environment Rating Scale. Statistical analysis was carried out using SPSS, with chi-square tests applied to examine associations between intelligence and various socio-economic variables. Findings indicated a significant association between children’s intelligence and mothers' occupation in Bhiwani (χ²=7.94*) but not in Hisar. Father's occupation showed a significant correlation with intelligence in both districts (Bhiwani: χ²=28.37*; Hisar: χ²=13.02*). Family income was also significantly related to intelligence in both Bhiwani (χ²=24.27*) and Hisar (χ²=9.49*). However, the number of siblings did not show any significant relationship with intelligence in either district. Additionally, the preschool environment was significantly associated with intelligence levels in both Bhiwani (χ²=15.95*) and Hisar (χ²=10.69*). These findings highlight the critical roles that economic background, parental occupation, and early childhood learning environments play in shaping cognitive development during early childhood.